2016
DOI: 10.1177/0363546515624467
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Genetic Predisposition to Anterior Cruciate Ligament Tear? A Systematic Review

Abstract: Although specific gene polymorphisms and haplotypes have been identified, it is difficult to come to a conclusion on the basis of the existing literature. Several sources of bias have been identified in these studies, and the results cannot be extrapolated to the general population. More studies are needed in larger populations of different ethnicities. Gene-gene interactions and gene expression studies in the future may delineate the exact role of these gene polymorphisms in ACL tears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 28 publications
0
56
0
Order By: Relevance
“…Nonetheless, studies available are not representative of the general population, limiting the extrapolation of results to general population 30. They concluded that larger, multicentric studies with different ethnic population should be conducted to better understand the role of genetic aetiology in ACL tears.…”
Section: Introduction and Basic Sciencementioning
confidence: 99%
“…Nonetheless, studies available are not representative of the general population, limiting the extrapolation of results to general population 30. They concluded that larger, multicentric studies with different ethnic population should be conducted to better understand the role of genetic aetiology in ACL tears.…”
Section: Introduction and Basic Sciencementioning
confidence: 99%
“…A best-evidence synthesis provides stronger evidence and takes a different approach to presenting the results than does a simple narrative summary. Consequently, the results and conclusions of the current analysis concerning the associations between genetic variants and ACL injury differ from and have greater methodological power than those of John et al [24]. Second, this review included two additional studies [30, 40].…”
Section: Discussionmentioning
confidence: 95%
“…John et al [24] recently published a systematic review on a topic similar to ours, albeit with some notable methodological differences between the two reviews. In an attempt to conduct more sensitive research, we searched more databases.…”
Section: Introductionmentioning
confidence: 99%
“…Modifiable risk factors are typically extrinsic factors such as footwear (Dowling, Corazza, Chaudhari, & Andriacchi, ) and playing surfaces (Orchard, Chivers, Aldous, Bennell, & Seward, ) and are more obvious and easily addressed than nonmodifiable risk factors. Nonmodifiable risk factors, which are mostly intrinsic and may put certain individuals at heightened risk of injury, include female gender (Hewett, Myer, & Ford, ; Myer, Ford, Paterno, Nick, & Hewett, ), genetic factors (John, Dhillon, Sharma, Prabhakar, & Bhandari, ; Smith et al, ), hormonal factors (Zazulak, Paterno, Myer, Romani, & Hewett, ), static lower limb alignment (Loudon, Jenkins, & Loudon, ; Nguyen, Shultz, & Schmitz, ), and narrow intercondylar notch size (Harner, Paulos, Greenwald, Rosenberg, & Cooley, ; Shelbourne, Davis, & Klootwyk, ). Knowledge of nonmodifiable risk factors is important as it enables the identification of those individuals most vulnerable to injury and to whom prevention training programmes should be directed.…”
Section: Introductionmentioning
confidence: 99%